Structure Elucidation of Soluble Dietary Fiber from Cauliflower (Dhaka University Journal of Science, 2016)
Arabinogalactan and rhamnogalactglucuronan were isolated from soluble dietary fiber (SDF) of cauliflower. The isolated SDF was fractioned into neutral and acidic parts by ion-exchange column chromatography using DEAESepharose Cl-6B gel. Structure elucidation of the isolated SDF polysaccharides were determined sugar analysis, 1HNMR, H-H COSY and TOCSY spectroscopic studies. Neutral fraction of cauliflower was found to be composed of galactose, arabinose and rhamnose whereas the acidic part was found to contain rhamnose, galactose, galacturonic and glucuronic acids. The main chain of the neutral fraction was found to be a 1,4-?-galactan where terminal rhamnose and arabinose residues were attached to the main chain at the 3-position of by ?-linkage.The main chain of the acidic fraction was composed of 1,4-b-linked galacturonic acid and 1,2-b-linked rhamnopyranose residues. ?- Glucuronic acid and ?-galactose were attached to the main chain of galacturonic acid at its 3-position.Dhaka Univ. J. Sci. 64(1): 83-88, 2016 (January)